THU0089 M-DAS28, DAS28 (CRP) and RAPID3 scores at baseline are good predictors of radiographic disease progression at 1 and 2 years: data from the ample trial. (15th June 2017) - Keystone, E; Ahmad, H; Yazici, Y; Muratti, E; Ye, J; Bergman, M
Abstract : Background: Clinicians rely on time-efficient, validated disease activity assessments to help predict disease progression accurately in patients (pts) with RA. The utility in predicting structural damage progression for the Routine Assessment of Patient Index Data 3 (RAPID3) 1 is largely unknown, while that of DAS28 (CRP) 2 and modified (M-)DAS28 have been previously reported. 3 Objectives: This post hoc analysis examined the relationship between baseline disease activity measures and their ability to predict structural damage progression in the Phase III AMPLE (NCT00929864 ) trial. 4 Methods: AMPLE was a randomized, investigator-blinded study in which MTX-experienced pts with active RA ≤5 years received SC abatacept 125 mg weekly or adalimumab 40 mg every 2 weeks in combination with stable-dose MTX. Logistic regression analysis was used to correlate the effect of disease activity at baseline on radiographic (X-ray) progression at Months (M) 12 and 24. Disease activity was assessed using M-DAS28, 3 DAS28 (CRP), RAPID3, CDAI and SDAI. Radiographs were scored using the modified Sharp/van der Heijde scoring system; progression was defined as change from baseline in total score greater than the smallest detectable change, which was calculated as SD/square root (2) x 1.96 (where SD is standard deviation of paired differences of change from baseline in total score between two readers). Results: Logistic regression analysis was carried out for all randomized and treated pts (abatacept, n=318; adalimumab, n=328). For these patients, M-DAS28, DAS28 (CRP) and RAPID3 at baseline were significant predictors of radiographic progression at M12 and M24, baseline SDAI was a significant predictor at M12 but not M24 and baseline CDAI was not a significant predictor at either time point (Table). Receiver operating characteristic curves showed that M-DAS28, DAS28 (CRP) and RAPID3 had higher predictive value (area under the curve) than CDAI or SDAI for radiographic progression at M12 and M24 (Table). There was no impact of treatment arm on predictors of radiographic outcomes. Conclusions: In this post hoc analysis, disease activity scores at baseline according to M-DAS28, DAS28 (CRP) and RAPID3 were good predictors of radiographic progression at M12 and M24 and were more predictive than other measures of disease activity tested, with M-DAS28 demonstrating the greatest degree of prediction. References: Yazici Y, et al. J Rheumatol 2008;35:603–9. Salaffi F, et al. BMC Musculoskelet Disord 2011;12:120. Baker JF, et al. Arthritis Rheumatol 2014;66:794–802. Schiff M, et al. Ann Rheum Dis 2014;73:86–94. Disclosure of Interest: E. Keystone Grant/research support from: Abbott, Amgen, AstraZeneca, Bristol-Myers Squibb, F. Hoffmann-La Roche, Janssen, Lilly, Novartis, Pfizer, sanofi-aventis, UCB, Consultant for: Abbott, AstraZeneca, Biotest, Bristol-Myers Squibb, Crescendo, F. Hoffmann-La Roche, Genentech, Janssen, Lilly, Merck, Pfizer, UCB, Speakers bureau: Amgen, Abbott, AstraZeneca, Bristol-Myers Squibb, F. Hoffmann-La Roche, Janssen, Pfizer, Sanofi, Genzyme, UCB, H. Ahmad Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Y. Yazici Grant/research support from: Genentech, Celgene, Bristol-Myers Squibb, Consultant for: Genentech, Celgene, Bristol-Myers Squibb, E. Muratti Employee of: Bristol-Myers Squibb, J. Ye Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Bergman Shareholder of: Pfizer, Johnson & Johnson, Consultant for: AbbVie, Bristol-Myers Squibb, Amgen, Celgene, Genentech, Pfizer, Janssen, Speakers bureau: Norvatis, Abbvie, Celegene